LANGUAGE AS ACTION: A PRAGMATIC PERSPECTIVE ON UNDERSTANDING LINGUISTIC MEANING - Suswandi; St. Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Traditional linguistic views often reduce language to a mere descriptive sign system that represents reality. However, the paradigm shift toward pragmatism demonstrates that language is fundamentally a tool for taking action within social dynamics. This article aims to analyze how language meaning is reconceptualized from mere representation to action, and the extent to which situational context determines the meaning of an utterance. This study employs a qualitative approach using a literature review method, analyzing philosophical and linguistic texts rooted in Wittgenstein’s concept of language games and the Speech Act Theory proposed by J.L. Austin and John Searle. The findings indicate that the meaning of an utterance is not merely embedded in its semantic and syntactic structure; rather, it is fundamentally shaped by its illocutionary and perlocutionary force during language use. Language does not simply describe the world, but actively alters and constructs social reality through performative acts such as promising, ordering, or declaring. Understanding language through a pragmatism perspective provides a more comprehensive framework for dissecting human interaction and is highly relevant for unraveling the complexities of modern communication, which relies heavily on contextual negotiation.